2021
DOI: 10.1519/ssc.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Physical Determinants of Golf Swing Performance: Considerations for Youth Golfers

Abstract: In the sport of golf, club head speed has been associated with higher skill levels in golfers and lower overall scoring. Research has shown that club head speed is an important measure of golf swing performance that can be enhanced with appropriate strength and conditioning interventions. Understanding the determinants of club head speed can help inform the design of testing batteries for talent identification and talent development of youth golfers. This review aims to highlight the current literature surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 103 publications
0
25
2
Order By: Relevance
“…Notably, CHS was the most reliable variable reported for both 6-iron and driver, which displayed excellent ICCs (ICC = 0.98 and 0.99, respectively) and very low CVs (1.3 and 0.9%) respectively. Notably, CHS is also the most commonly reported golf swing variable reported in the scientific literature (24). Because of the ability of the TrackMan to produce ball speed, carry distance, and total distance data reliably and instantaneously alongside CHS, these variables can be confidently used by practitioners to assess golf swing performance in a single session.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CHS was the most reliable variable reported for both 6-iron and driver, which displayed excellent ICCs (ICC = 0.98 and 0.99, respectively) and very low CVs (1.3 and 0.9%) respectively. Notably, CHS is also the most commonly reported golf swing variable reported in the scientific literature (24). Because of the ability of the TrackMan to produce ball speed, carry distance, and total distance data reliably and instantaneously alongside CHS, these variables can be confidently used by practitioners to assess golf swing performance in a single session.…”
Section: Discussionmentioning
confidence: 99%
“…This finding reflects recent literature that has highlighted that these training modalities can enhance CHS, ball speed and carry distance when delivered as part of a periodised strength and conditioning programme. 3,4,40 Most of the respondents 'strongly' and 'somewhat agreed' that exercises that mimic the golf swing can improve golf performance in youth golfers. Within the research, exercises such as rotational medicine ball throws have indeed been shown to improve golf swing performance, 41 and these exercises are often used on the grounds of movement specificity.…”
Section: Perceptions and Approaches Of Strength And Conditioning For ...mentioning
confidence: 99%
“…11 Warm-ups are recognised as an important means to acutely enhance athletic performance via pathways that increase the rate of force development, strength and power which have been highlighted to be key determinants of golf swing performance. 3 For example, research has shown that a dynamic warm-up including a range of strength and power exercises can significantly increase CHS in junior golfers. 12 Previous research has surveyed the warm-up behaviours of mid to high handicap, adult male, amateur golfers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations